2020
DOI: 10.1111/pde.14101
|View full text |Cite
|
Sign up to set email alerts
|

Oral erosions associated with surreptitious marijuana vaping in an adolescent boy

Abstract: A 15‐year‐old boy presented with painful ulcerations affecting the oral mucosa that were eventually attributed to marijuana vaping. In this case report, we highlight cannabis vaping as a potential cause of oral erosions due to injury and chronic inflammation of the oral mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Other studies have also suggested that cannabis use increases the risk of developing intraoral soft tissue or mucosal lesions [ 38 ]. However, significant heterogeneity exists between studies insofar as study designs and definitions of oral lesions are concerned [ 51 , 52 ], and most studies yielded inconclusive findings [ 53 ] or were limited to case reports [ 40 , 41 , 54 ]. Given our findings, it may be warranted for future studies to further assess the frequency and duration for which these lesions appear, as well as investigate the mode of cannabis consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also suggested that cannabis use increases the risk of developing intraoral soft tissue or mucosal lesions [ 38 ]. However, significant heterogeneity exists between studies insofar as study designs and definitions of oral lesions are concerned [ 51 , 52 ], and most studies yielded inconclusive findings [ 53 ] or were limited to case reports [ 40 , 41 , 54 ]. Given our findings, it may be warranted for future studies to further assess the frequency and duration for which these lesions appear, as well as investigate the mode of cannabis consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on periodontal disease and found cannabis use to be associated with poorer periodontal health [ 30 , 31 , 32 , 33 , 34 ]. Other studies have explored cannabis use and other oral health outcomes such as caries [ 35 , 36 , 37 ], soft tissue oral lesions [ 38 , 39 , 40 , 41 ], and salivary changes [ 42 , 43 ], though findings were inconsistent, confounded by tobacco use, and limited by sample size. To our knowledge, no studies have yet focused solely on adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found that the heated elements in e-cigarettes or vape pens can have negative effects on the oral tissues due to released byproducts that can lead to increased levels of oral irritation and inflammatory responses. 13,16 Inflammatory responses by use of these products may create swelling of the lips, and thereby expand the grooves, changing the appearance of a collected lip print. Additionally, burns or explosions, due to spontaneous combustion of the heating element in these devices, can scar the vermillion zone and cause permanent changes to the lip print appearance.…”
Section: Ta B L E 1 Self-reported Parafunctional Oral Habits Among In...mentioning
confidence: 99%
“…1,[5][6][7][8][9] The literature also suggests that lip prints may be altered as the result of adaptive muscle functions including activities that involve frequent pursing of the lips. 5,[10][11][12][13][14][15][16][17][18][19] Pursing the lips causes a contraction of the multilayered and complex orbicularis oris muscle, 17 which is primarily responsible for the shape, form, and movement of the lips. 18 Over time and with exaggerated use for parafunctional oral habits, this muscle may exacerbate the formation of deep wrinkles of the vermillion zone.…”
mentioning
confidence: 99%
See 1 more Smart Citation